Analisis Pelaksanaan Pembelajaran Pendidikan Agama Islam Berbasis Blanded Learning di SMP Negeri 40 Medan - Musthopa Husein; Munawir Pasaribu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Blended Learning method is a promising alternative for enriching the learning experience. Given the challenges and opportunities in implementing Blended Learning in schools, this research aims to make a constructive contribution to schools, teachers and the government. The method used in this research is a qualitative research procedure to describe the character of the problem being monitored. explains that qualitative research aims to obtain a complete reflection of things in the minds of the people being supervised). In conclusion, the implementation of Blended Learning at SMP Negeri 40 Medan offers a learning approach that combines face-to-face interaction in class with the use of technology and online platforms. Although the majority of students respond positively to the flexibility of Blended Learning, there are several challenges that need to be overcome, especially regarding unequal access to technology and time management.